Reinternação de pacientes com síndrome coronariana aguda e seus determinantes - Oliveira, Larissa Marina Santana Mendonça de (2018)
Introduction: Acute Coronary Syndrome (ACS) is responsible for raising admissions numbers and hospital readings. Patients are associated with increased costs to the patient and the health system, as well as access to hospital mortality rates. Objective: To investigate rehospitalization factors in patients with ACS. Methodology: This is a retrospective study of patients of both sexes, adults and elderly, diagnosed with ACS. The records of health and health cases were evaluated in relation to cardiology, the occurrence of rehospitalization, the time between admissions and the use of medications at the time of rehospitalization, up to one year after admission for ACS. Logistic regression was used to evaluate the predictive variables of rehospitalization. Results: The occurrence of readmissions was 21.46% (n = 115) and the mean period between hospitalizations was 122.74 (SD 112.14) days. Most patients were male (64.0%), mean age was 63.15 years (SD 12.26) years, 7% had readmission and 68.7% had more than one readmission in 01 year. The cardiovascular causes, among them, the recurrence of ACS, were the most prevalent among hospital readmissions. Public utility (OR 0.46) and the diagnosis of CHF (OR 1.81) were associated with reintroduction following multiple logistic regression. Conclusion: As the rehospitalizations are therapeutic and they return to help health professionals and are associated with the recurrence of the ACS event and the type of care.